Adaptação do Personal Assessment of Intimacy in Relationships Scale (PAIR) para a população Portuguesa: Estudo das suas características psicométricas - Moreira, Helena (2009)
The intimacy is one of the main components of a close interpersonal relationship (Clark & Reis, 1988). Many researchers have dedicated to the study of this concept, but there is not still a consensus definition. For Schaefer and Olson (1981), intimacy is a process and an experience, which results from the disclosure of intimate matters and sharing of experiences. Starting from a multidimensional conceptualization, the authors constructed the Personal Assessment of Intimacy in Relationships Scale (PAIR), to assess five areas of intimacy: emotional, intellectual, social, recreational and sexual. This study aimed to adapt and evaluate the psychometric behaviour of PAIR, in a sample of the Portuguese population. The original factor structure was not confirmed. The factor analysis resulted in a solution composed by three factors, which received the designations of Personal Validation, Communication and Open to the Exterior. The results showed also a good reliability and validity of the instrument.